International negotiators adopt CCAFS recommendations in the process of developing a new international system of plant germplasm exchange - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The intergovernmental and stakeholder group in charge of international negotiations for enhancing the multilateral system of access and benefit-sharing under the Plant Treaty introduced content into the negotiating text that will be used as the basis of negotiations in 2018 based on submissions from CCAFS in 2017. The enhanced multilateral system eventually adopted by all the parties to the Plant Treaty is therefore expected to take into consideration and integrate elements and aspects of crucial importance for CCAFS.